One-year ecological momentary assessment of alcohol use, mood, and stress among individuals with alcohol use disorder during SARS-CoV-2 pandemics: a gender-specific reflection - Wenzel, Julia G.; Reichert, Markus; Zech, Hilmar; Wedemeyer, Friederike; Deeken, Friederike; Spitta, Gianna; Bach, Patrick; Lenz, Bernd; Ebner-Priemer, Ulrich; Kiefer, Falk; Rapp, Michael A.; Walter, Henrik; et al. (European archives of psychiatry and clinical neuroscience, 2025)
Alcohol consumption (AC) is a leading risk factor for death, morbidity, and disability worldwide. Gender-specific differences in AC and its moderators, which may serve as markers for preventing severe alcohol use disorders (AUD), showed inconsistent results. Additionally, the impact of COVID-19-related lockdowns on these differences remains unclear. We examined gender-specific differences in short- and long-term factors affecting AC in individuals at risk for alcohol dependence, focusing on mood, stress, and the influence of restriction-dependent lockdown phases. 358 subjects with AUD aged 16 to 65 were studied over one year. Daily electronic diaries and monthly questionnaires were conducted from 10/01/2020 to 09/30/2021, assessing real-world trajectories of AC, mood (MDMQ), and stress (PSS-10) during Germany’s second COVID-19 wave. Multi-level models were used to assess associations between these measures and with several within- and between-subject variables. During lockdown, women experienced lower and even decreasing mood (valence: β = − 0.2, p < .039; calmness: β = − 0.3, p < .010), while men’s mood increased from the most restrictive lockdown phase (valence: β = 0.2, p < .001; calmness: β = 0.3, p < .001) to post-lockdown (valence: β = 0.5, p < .001; calmness: β = 0.6, p < .001). Stress increased earlier (β = 0.8, p < .001) and more prolonged (β = 0.4, p = .021) in women than in men. For both genders, daily mood was positively associated with daily AC (valence: β = 0.6, p = .004; calmness: β = 0.4, p = .013), leading to stronger drinking on days with elevated mood. Conversely, average mood was negatively associated with average AC (valence: β = − 1.6, p = .011; calmness: β = − 1.2, p = .041), indicating higher overall consumption with worse overall mood. Our findings highlight the need for interventions targeting mental distress in women with AUD during pandemics, as this group faces increased mental burden during social isolation and increased risk of alcohol dependence during persistent distress.
Online veröffentlicht: 19. November 2024
Gesehen am 01.04.2025